2016
DOI: 10.5713/ajas.16.0429
|View full text |Cite
|
Sign up to set email alerts
|

Partial dehulling increases the energy content and nutrient digestibility of barley in growing pigs

Abstract: ObjectiveThe hull attached to the barley kernel can be mechanically removed thus reducing the fiber content of the barley. This experiment was carried out to evaluate the effects of partial dehulling on the nutrient digestibility as well as the digestible energy (DE) and metabolizable energy (ME) content of barley in pigs.MethodsTwo hulled barley samples (high fiber barley [HF] and low fiber barley [LF]) with either high or low fiber contents were obtained from the Hubei and Jiangsu Provinces of China. A porti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 26 publications
1
2
0
1
Order By: Relevance
“…There were no differences in the daily GE intake and the daily loss of GE in feces and urine among pigs fed the three barley grains ( Table 5 ). This is consistent with the results reported by Wang et al [ 21 ] who showed that no differences were found in daily balance of gross energy between two barley cultivars with different fiber content. The DE and ME in Canadian barley were higher (p<0.01) than in French barley and did not differ from the Australian barley.…”
Section: Resultssupporting
confidence: 93%
“…There were no differences in the daily GE intake and the daily loss of GE in feces and urine among pigs fed the three barley grains ( Table 5 ). This is consistent with the results reported by Wang et al [ 21 ] who showed that no differences were found in daily balance of gross energy between two barley cultivars with different fiber content. The DE and ME in Canadian barley were higher (p<0.01) than in French barley and did not differ from the Australian barley.…”
Section: Resultssupporting
confidence: 93%
“…Hvelplund (1985) also reported a lower small intestinal digestibility of RUP in some feedstuffs due to higher proportion of cell wall bound nitrogen content. Another study likewise suggested a negative correlation between the fiber content and nutrient digestibility (Wang et al, 2017).…”
Section: Digestion Of Cp and Aa In The Small Intestinementioning
confidence: 91%
“…Decorticating of grains is a practical tool for increasing the digestible energy content of dairy cow diets without altering the forage-to-concentrate ratios (Yang et al, 1997;Wang et al, 2017). Decortication resulted in the expected changes in composition and in vitro digestibility (Panah et al, 2019).…”
Section: Processing Of Oatmentioning
confidence: 99%
“…Therefore, the application of heat treatment (e.g., roasting) could be a possible way to reduce CP rumen degradation [65]. The husking of cereals is a practical tool to increase the digestible diet energy for dairy cows without altering the forage-concentrate ratio [66]. Table 4 shows oat protein degradability.…”
Section: Oatsmentioning
confidence: 99%